PENGARUH GENDER, PENGALAMAN, KEAHLIAN AUDITOR DAN TEKANAN KETAATAN TERHADAP AUDITOR JUDGEMENT DENGAN KOMPLEKSITAS TUGAS SEBAGAI VARIABEL MODERASI PADA BPK RI JAWA TENGAH - Aditya Purba Nugraha; Indira Januarti (Diponegoro Journal of Accounting, 2015)
Audit judgment is one way of looking auditors in response to information that affects decision-making documentation of evidence and the auditor's opinion on the financial statements of an entity. Judgement is an activity that is always used auditors in any audit process, the auditor must continue to hone their judgment. Proper judgment whether or not an auditor will determine the quality of audit results and opinions to be issued by the auditor. The purpose of this study was to analyze the factors that affect the auditor's judgment on BPK Central Java. The study population was auditor at BPK RI Central Java. The sampling method used in this research is purposive sampling method. The sample used in this study were 120 people at the BPK auditors Central Java. The data used are primary data using questionnaires. The analysis technique used is multiple linear regression analysis. Based on the results of the study, gender and experience do not affect the Auditor's judgment, while the expertise of auditors and pressure obedience positive effect on auditor judgment. The complexity of the task can be concluded not moderate influence between the variables of gender, experience, expertise and pressure auditor adherence to auditor judgment